2022
DOI: 10.3390/polym14081629
|View full text |Cite
|
Sign up to set email alerts
|

Application of Red Cabbage Anthocyanins as pH-Sensitive Pigments in Smart Food Packaging and Sensors

Abstract: Anthocyanins are excellent antioxidant/antimicrobial agents as well as pH-sensitive indicators that provide new prospects to foster innovative smart packaging systems due to their ability to improve food shelf life and detect physicochemical and biological changes in packaged food. Compared with anthocyanins from other natural sources, red cabbage anthocyanins (RCAs) are of great interest in food packaging because they represent an acceptable color spectrum over a broad range of pH values. The current review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 76 publications
0
50
0
Order By: Relevance
“…RCE is a rich source of anthocyanins. Based on the chemical structure of anthocyanin ( Figure 4 a), it is very similar to one of the flavonoids of honey, apigenin ( Figure 4 b) [ 40 , 41 ]. Moreover, regarding the high loading percentage of honey (400% with respect to SA) and very low incorporation of RCE, one might expect that the FTIR spectrum of CA/H/RCE would not change compared to CA/H.…”
Section: Resultsmentioning
confidence: 99%
“…RCE is a rich source of anthocyanins. Based on the chemical structure of anthocyanin ( Figure 4 a), it is very similar to one of the flavonoids of honey, apigenin ( Figure 4 b) [ 40 , 41 ]. Moreover, regarding the high loading percentage of honey (400% with respect to SA) and very low incorporation of RCE, one might expect that the FTIR spectrum of CA/H/RCE would not change compared to CA/H.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, colourimetric pH sensor films could be commercialised by incorporating sago starch and anthocyanin extracted from Brassica oleracea to serve as sensors that respond rapidly and inform customers about the condition and quality of the packaged food. Even while anthocyanin-based indicators can accurately predict the food shelf-life in a variety of products at a lab scale, the manufacturing processes for this kind of sensor still limit their industrial output [ 42 ]. In addition, it is suggested that some modifications need to be completed on this starch-based film to control the release of anthocyanin by the addition of other natural resources to hold the anthocyanin longer in the starch matrix [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: ANT, anthocyanin; BET, betalains; CBO, clove bud oil; CUR, curcumin; MRSA, Man, Rogosa, and Sharpe agar; PVA, polyvinyl alcohol. process (Abedi-Firoozjah et al, 2022;Azlim et al, 2022;Shao et al, 2021). As the packaged seafood product starts to deteriorate, the pH of the closed food packaging environment will correspondingly increase over time.…”
Section: Freshness Indicatorsmentioning
confidence: 99%